مقـــاربة تربويــة تحليليـة لمنـاهج الجيـل الثـاني في المنظومة التربوية الجزائرية - بوفاتح محمد; بن سماعيل فاطمة (My University, 2018)
إن المؤسّسات المجتمعية بمختلف أشكالها تسعى إلى تحقيق مرام ذات جودة عالية تسمو بها مع مصاف منحى التطور التكنولوجي، ولعل أهمها التربية والتعليم الذي يعد أقوى قطاع مؤسّساتي ؛إذ يتطلّع إلى اهتمامات المجتمع وفلسفته، باعتباره مؤسسة تعليميّة تهدف إلى إعداد أفراد المجتمع إعدادا جيّدا، وتوجيههم وفق الرؤى المستقبلية، لهذا هدفت المنظومة التربوية الجزائرية إلى تجسيد مسعى جودة المخرجات ببناء مناهج تربوية جديدة "مناهج الجيل الثّاني"،كون المناهج تحتل موقعا استراتيجيا في العملية التعليمية، والصورة العاكسة والعملية لأهداف التربية واتجاهاتها. انطلاقا من هذا الطرح العام تسعى هذه الدراسة إلى توضيح الأهداف العملية لكتابة مناهج الجيل الثاني وذلك بإبراز المحاور الكبرى المهيكلة لها، وأهم المفاهيم القاعدية الجديدة المتداولة فيها مع مقارنة بينها وبين المناهج السابقة، وكذا مدى انسجامها مع القانون التوجيهي للتربية. Abstract The community institutions in all their forms and the diversity of their structures seek to achieve high quality goals with high technological development ,Perhapsthe most important education is the most powerful sector of my institutions looking to the interests of the community and its goals and philosophy . As an educational institution aimed at preparing the menders of society well and guiding them according to the future narration . For this purpose of the Algerian educational system to reffect the effort to quality output to build up a new didactic courses « Second generation curriculum» occupies an important educational process and the reflective image of the educational goals. From the public offering seeking this study to clarify the goals of the process book curricula second generation . In order to highlight asces of the great structured. The most important concepts traded the comparision between the curriculum as well as with law guideline for education .
Keywords: المناهج، ، مناهج ماقبل الإصلاح، مناهج الجيل الأول، مناهج الجيل الثاني، العملية التعليمية. Keywords: Curriculum, Pre-reform curricula, First-generation curricula, Second-generation curricula, Educational process.